Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 7 - Section 7.3 - Simplifying Radical Expressions - Exercise Set - Page 433: 51


$x^{4}\sqrt[3] (50x^{2})$

Work Step by Step

$\sqrt [3] (50x^{14})=\sqrt [3] (x^{12}\times50x^{2})=\sqrt [3] (x^{12})\times \sqrt[3] (50x^{2})=x^{4}\sqrt[3] (50x^{2})$ We know that $\sqrt[3] (x^{12})=x^{4}$, because $(x^{4})^{3}=x^{4\times3}=x^{12}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.